A fatal infection caused by sequence type 398 methicillin-resistant Staphylococcus aureus carrying the Panton-Valentine leukocidin gene: A case report in Japan. Issue 7 (July 2015) - Koyama, Hiroshi; Sanui, Masamitsu; Saga, Tomoo; Harada, Sohei; Ishii, Yoshikazu; Tateda, Kazuhiro; Lefor, Alan Kawarai
Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) has now been recognized as a common pathogen in the community. Sequence type (ST) 398 MRSA is generally considered as an emerging zoonotic agent spreading among livestock and personnel who have direct contact with animals, mainly in Europe. A 37-year-old Chinese woman receiving steroid therapy for systemic lupus erythematosus with general fatigue and myalgia was brought to the emergency department in critical condition. Her condition deteriorated despite aggressive management and she died on day 7. Her blood culture revealed ST398 MRSA-SCC mec V with Panton-Valentine Leukocidin (PVL) gene. This is the first case report of a fatal infection caused by this lineage. According to the results of molecular analyses, the isolate from this particular patient's blood was genetically close to a lineage detected in China, and is less likely to be related to an animal-associated lineage.